Palladium-catalyzed arylation of 2H-chromene: a new entry to pyrano[2, 3-c]carbazoles1. Issue 35 (21st September 2015) - Ranjith Reddy, K.; Siva Reddy, A.; Dhaked, Devendra K.; Rasheed, S. K.; Pathania, Anup Singh; Shankar, Ravi; Malik, Fayaz; Das, Parthasarathi
<x xml:space="preserve">Abstract</x> Various pyrano[2, 3-c]carbazoles are synthesized in high yields over five steps from commercially available resorcinol. Palladium-catalyzed arylation remains a key step in this novel strategy. The versatility of this protocol has been demonstrated by the first total synthesis of naturally occurring carbazole clauraila C.